Biomarkers of septic shock to predict hospital mortality in major burns undergoing antimicrobial therapy during the systemic inflammatory response syndrome - Silvia RCJ Santos; Léonard de Vinci Kanda Kupa; Mauro Jorge Santos; Thaís Vieira de Camargo; Aline Sandre Gomides Abad; Gabriela Aparecida Ferreira; Thiago Câmara de Oliveira; Débora Cristina Sanches; Edvaldo Vieira de Campos; João Manoel Silva; Maria Severina dos Santos; Nilo José Coêlho Duarte; et al. (2024)
Introduction: Septic shock is one of the leading causes of death among critically ill patients in the Intensive Care Unit (ICU), including severely major burned patients. Rapid diagnosis and early initiation of effective antimicrobial therapy are the main challenges. The role of leukocytes as the neutrophil/lymphocyte ratio (NLR) and various systemic inflammatory indices, include serum levels of interleukin-6 (IL-6), procalcitonin (PCT) and c-reactive protein (c-RP) are the informative laboratory markers in this regard respect. Subject: Monitoring of serum levels of interleukin (IL6), procalcitonin (PCT) and C-reactive protein (C-RP), including among leukocytes the index neutrophil/lymphocyte ratio (NLR), proposed previously, investigated at the first septic shock of major burns undergoing meropenem therapy recommended in hospital, during the systemic inflammatory response syndrome (SIRS), after ICU admission. Fundamental aim of study was to investigate the relationship, and contribution of these biomarkers at the early versus late stage of septic shock, as well as to determine the diagnostic performance of them in major burn patients that could impact outcome. Methods: In this prospective open label study, a total of 30 major septic burn patients with renal function preserved, augmented or with acute kidney injury (AKI) was enrolled at the first septic shock after accident and ICU admission, based on systemic inflammatory response syndrome (SIRS) criteria. All patients had been selected from the ICU of Plastic Surgery and Burn Unit of tertiary public hospital of Medical School, University of Sao Paulo, SP, Brazil. Laboratory data with known clinicopathological parameters were recorded. Serum levels of IL6, PCT, c-RP and NLR from the blood count were evaluated. Inflammatory biomarkers such as c-RP, PCT and IL6 in serum were performed on the COBAS 8000 series (c-RP) or COBAS E411 series analyzer for PCT, IL6 (Roche, registered trademark), neutrophil to lymphocyte ratio (blood count) was measured using a Hematology Analyzer (SYSMEX brand). Therapeutic serum measurements of combined therapy with antibiotics (ATB) were done by comparison of coverage at the earlier versus late stage of septic shock. Results: A significant difference was found in NLR, IL6, PCT and c-RP in surviving patients (n=20) comparing data obtained in early stage versus late-stage SIRS (p<0.05) in major burns with positive bacteriological cultures. On the other hand, there was no significant difference between the NLR and IL6 periods, which occurred when comparing data in the early versus late stage of SIRS in non-survival patients, who died between 7 and 10 days of antimicrobial therapy. There was an increasing trend in serum levels of NLR and IL6, PCT and c-RP in large burns, dependent on the timing of septic shock stages, with diagnostic value as early appearance of biomarkers. On the other hand, we recorded that the association of NLR and IL6 produces better diagnostic value in predicting ICU mortality than PCT or c-RP. Conclusion: It was shown in this pilot study that elevated NLR and increasing serum levels of IL6, PCT, c-RP occurred during SIRS in septic patients’ major burns. So, the combined use of these biomarkers may play a potential role in the early diagnosis of septic shock for adequate initial therapy of these ICU patients. Combined biomarkers (NLR-IL6) can further predict ICU mortality of septic patients with acute kidney injury occurring during SIRS. Finally, a prospective multicenter study in a large cohort can be performed to confirm the data obtained in this investigation.